Possible Consequences of Climate Change on Survival, Productivity and Reproductive Performance, and Welfare of Himalayan Yak (Bos grunniens) - Sapkota S; Acharya KP; Laven R; Acharya N (MDPI (Basel, Switzerland), 2022)
Yak are adapted to the extreme cold, low oxygen, and high solar radiation of the Himalaya. Traditionally, they are kept at high altitude pastures during summer, moving lower in the winter. This system is highly susceptible to climate change, which has increased ambient temperatures, altered rainfall patterns and increased the occurrence of natural disasters. Changes in temperature and precipitation reduced the yield and productivity of alpine pastures, principally because the native plant species are being replaced by less useful shrubs and weeds. The impact of climate change on yak is likely to be mediated through heat stress, increased contact with other species, especially domestic cattle, and alterations in feed availability. Yak have a very low temperature humidity index (52 vs. 72 for cattle) and a narrow thermoneutral range (5-13 °C), so climate change has potentially exposed yak to heat stress in summer and winter. Heat stress is likely to affect both reproductive performance and milk production, but we lack the data to quantify such effects. Increased contact with other species, especially domestic cattle, is likely to increase disease risk. This is likely to be exacerbated by other climate-change-associated factors, such as increases in vector-borne disease, because of increases in vector ranges, and overcrowding associated with reduced pasture availability. However, lack of baseline yak disease data means it is difficult to quantify these changes in disease risk and the few papers claiming to have identified such increases do not provide robust evidence of increased diseases. The reduction in feed availability in traditional pastures may be thought to be the most obvious impact of climate change on yak; however, it is clear that such a reduction is not solely due to climate change, with socio-economic factors likely being more important. This review has highlighted the large potential negative impact of climate change on yak, and the lack of data quantifying that impact. More research on the impact of climate change in yak is needed. Attention also needs to be paid to developing mitigating strategies, which may include changes in the traditional system such as providing shelter and supplementary feed and, in marginal areas, increased use of yak-cattle hybrids.
Keywords: climate change; diseases; heat stress; temperature; welfare; yak